Desenvolvimento de néctar à base de mamão (Carica papaya L.) adicionado de inulina e oligofrutose - Braga, Héberly Fernandes [UNESP] (2013)
The demand for food and functional ingredients has increased, in particular by the prebiotics. The incorporation of inulin and oligofructose in fruit drinks, as nectars, is an alternative to increase nutritional value to products. Among fruits, the papaya is an excellent choice because of its easy cultivation, high productivity, low cost, high nutritional value and, particularly, the shortage of this fruit nectar in the Brazilian market. The study aimed to develop papaya nectars with different concentrations of sugar, oligofructose and inulin. Nectars were prepared with 6, 8, 10 and 12% sugar (without fructan) and the ideal sweetness of sugar was determined. From the formulation considered ideal sweetness, the mixtures modeling methodology was applied to assess the effects of the interaction between sugar, oligofructose and inulin on the acceptance sensory and chemical characteristics of papaya nectars (dependent variables). The sensory acceptance regarding to appearance, aroma, viscosity, flavor, sweetness and overall evaluation and purchase intent was evaluated, using a nine point hedonic scale and categorical scale of five points, respectively. The results of sensory acceptance were also assessed by cluster analysis and principal component analysis to construct internal preference maps. The formulations were characterized regarding to soluble solids and total, titratable acidity, total sugars, ash and pH. The best formulation for overall assessment was monitored for two weeks for pH, titratable acidity, mesophilic, psychrotrophic, yeasts and molds, total and fecal coliforms. The formulation with 12% sugar was considered ideal for sweetness by 36% of the panelists. The interaction between the ingredients sugar, oligofructose and inulin influenced the acceptance for the taste and the sweetness of the nectar, and the formulation with 6% sugar and 6% inulin was the most acceptable for these attributes. The preference for attributes of this ...